Implementasi Sistem Informasi Manajemen dalam Pengelolaan Administrasi di Pondok Pesantren Musthafawiyah Purba Baru - Siti Fatimah Rahmila; Novebri Novebri (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research investigates the implementation of the Management Information System (SIM) in administrative management at the Musthafawiyah Purba Baru Islamic Boarding School, Mandailing Natal Regency. This study found that Islamic boarding schools have adopted intranet, internet and extranet-based SIMs to speed up the administration process. However, this research also identified challenges such as limited information technology capabilities among users. Through descriptive qualitative research methods using interview, observation and documentation techniques, this research highlights the importance of MIS in supporting decision making, data processing and the effectiveness of educational management in Islamic boarding schools. This research recommends increasing human resource training and strengthening technological infrastructure to increase the effectiveness of SIM in supporting Islamic boarding school administration.